2016
DOI: 10.1136/esmoopen-2016-000126
|View full text |Cite
|
Sign up to set email alerts
|

Upper tract urothelial carcinoma: a different disease entity in terms of management

Abstract: Upper tract urothelial carcinomas (UTUCs) consist of 5%–10% of all urothelial carcinomas, the rest being urothelial carcinomas of the bladder (UCB). There is increasing evidence to show that UTUC is a distinct disease entity from UCB based on phenotypical and genotypical (genetic and epigenetic) differences. This may account for why the natural history of UTUC is different from that of UCB, with >60% of UTUCs and only 15%–25% of UCB presenting with invasion at diagnosis. Management of UTUC is thus different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 47 publications
0
66
0
Order By: Relevance
“…Bladder cancer is highly varied, and non-muscle-invasive bladder cancer and muscle-invasive bladder cancer are its two major subsets. Approximatedly 15–25% of non-muscle-invasive bladder cancer will progress to muscle-invasive bladder cancer [ 2 ]. Muscle-invasive bladder cancer would rapidly progress and metastasize.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer is highly varied, and non-muscle-invasive bladder cancer and muscle-invasive bladder cancer are its two major subsets. Approximatedly 15–25% of non-muscle-invasive bladder cancer will progress to muscle-invasive bladder cancer [ 2 ]. Muscle-invasive bladder cancer would rapidly progress and metastasize.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are distinct epidemiological and clinicopathological differences between the two suggesting different genetic phenotypes. 6 Insight into these molecular pathways is important as it holds the promise for potential targets for therapy.…”
Section: Molecular Pathwaysmentioning
confidence: 99%
“…4 However, the management of lower tract urothelial carcinoma remains more extensively studied in the literature by far compared to UTUC, which therefore informs the optimal management strategies for UTUC more by inference than by direct evidence especially for systemic therapies; 5 yet we know they should be really be considered "distinct entities in terms of management". 6 A retrospective review of the MD Anderson Cancer Center's experience in the United States from 1986 to 2004 found that there had been no appreciable improvement in disease-specific survival of UTUC over two decades and called for a change in the treatment paradigm. 7 With improving knowledge of the molecular tapestry of UTUC 8,9 and with more options in the therapeutic arsenal, the future holds greater promise for the optimal management of UTUC.…”
Section: Introductionmentioning
confidence: 99%
“…Since UTUC is considered an aggressive disease with >60% of cases presenting with invasion at diagnosis, risk stratification is advisable in order to choose the proper surgical and/or medical treatment option ( 11 ). Similarly to NMIBC, clinical and pathological parameters (i.e., tumor multifocality, size, stage and grade, patient’s gender, and so on) continue to play a role even though studies addressing their role have yielded conflicting results and limited evidence overall ( 12 , 13 ).…”
Section: Utuc and Ubc: Who Is The Cat And Who Is The Tiger?mentioning
confidence: 99%